Homogeneous polyporus polysaccharide inhibits bladder cancer by polarizing macrophages to M1 subtype in tumor microenvironment - Wenyu Jia; Siwan Luo; Gena Lai; Shiqi Li; Shuai Huo; Meifang Li; Xing Zeng (BMC, 2021)
Abstract Background Polyporus polysaccharide (PPS), an active ingredient of traditional Chinese medicinal Polyporus umbellatus, has multiple biological functions, such as anti-cancer, immune-regulating and hepatoprotective activities. The purpose of this study was to investigate the mechanism of homogeneous polyporus polysaccharide (HPP) activated macrophages in the treatment of bladder cancer. Methods 100 ng/mL Phorbol myristate acetate (PMA) was used to induce THP-1 human leukemic cells as a macrophage model. Then macrophages derived from THP-1 were treated with different concentrations of HPP (1, 10 and 100 μg/mL). Flow cytometry and RT-PCR were used to detected the expression of CD16, CD23, CD86, CD40 and interleukin (IL)-Iβ, iNOS mRNA. ELISA was used to test the change of IL-1β and TNF-α in macrophage after the treatment with HPP. The conditioned medium from HPP-polarized macrophages was used to detect the effect of activated macrophages on bladder cancer. MTT assay, 5-ethynyl-2'-deoxyuridine assay, flow cytometry, Transwell assay, and Western blot analysis were used to detect the effects of polarized macrophages on the viability, proliferation, apoptosis, and migration of bladder cancer cells. Western blot was also used to analysis the change of JAK2/NF-κB pathway protein. Results HPP promoted the expression of pro-inflammatory factors, such as IL-Iβ, TNF-α and iNOS, and surface molecules CD86, CD16, CD23, and CD40 in macrophages and then polarized macrophages to M1 type. Results demonstrated that activated macrophages inhibited the proliferation of bladder cancer cells, regulated their apoptosis, and inhibited migration and epithelial-mesenchymal transformation (EMT). JAK2/NF-κB pathways were downregulated in the anti-bladder cancer process of activated macrophages. Conclusion The findings indicated that HPP inhibited the proliferation and progression of bladder cancer by the polarization of macrophages to M1 type, and JAK2/NF-κB pathway was downregulated in the process of anti-bladder cancer.